Shannon entropy and energy of H-atom confined in fullerene cage: Effect of External electric field - Brijender Dahiya; Bhavna Vidhani; Norberto Aquino; Vinod Prasad (Chemical Physics Impact)
This study examines the energy and entropic properties of a hydrogen atom confined within a fullerene cage, using two potential models: the Square Well (SW) and Gaussian Potential (GP). The fullerene cage sizes considered correspond to C@36 (C36) and C@60 (C60). Key factors influencing the energy levels and total Shannon entropy include the radius of the fullerene cage, the strength of the confining potential, and the shell width of the cage. Additionally, the impact of an external electric field on these properties is analysed in detail. Notably, the electric field introduces avoided crossings in various states, which were previously observed only in s-states due to variations in the confining potential strength. This study underscores the complex interplay between the confining potential strength, cage width, and perturbations induced by the electric field.